Inclusive policing from the inside out - Workman-Stark, Angela (Advanced sciences and technologies for security applications, 2017)
This book provides a roadmap for how police services can address incivility in the workplace and become more inclusive from the inside out. In the past few years policing has come under increased scrutiny due to a number of police-involved shootings and in-custody deaths, where systemic racism, the inability to effectively confront persons suffering from mental illness, and excessive use of force have been perceived by civil rights groups to play a significant factor. These deaths and the subsequent public outcry have led to various constituents questioning the legitimacy of the police. The book incorporates real stories of police officers and case studies of select police organizations. A look inside a number of these departments has identified an equal concern for incivility within the workplace in the form of gender and ethnic harassment and discrimination. The costs of workplace incivility can be significant as workplace victims are not only likely to decrease their work effort, quality of work, and their level of commitment to the organization, they are also likely to mistreat others in the workplace and to take their frustrations out on those they serve. While these costs have a significant impact for police organizations, incivility by police officers against members of the public can have a much greater impact in terms of eroding perceptions of police legitimacy. This book will take a unique approach in providing a model for police organizations to pursue in becoming more inclusive. To this end, this book will be very relevant for police practitioners, reform advisors, researchers, and graduate-level course in special topics